Establishment of Quality Standards for Raw Material of Cyanthillium cinereum (L.) H. Rob - Charoonratana, Tossaton; Pongnuruk, Ketkanok; Puttarak, Panupong (Natural Products Journal, The, 2021)
Introduction: Cyanthillium cinereum has long been used in Thai traditional medicine. However, the standard information of C. cinereum raw material has not been established. Objective: This study aimed to present the standard information of C. cinereum raw material. Material and methods: The microscopic and macroscopic characteristics, the physicochemical analysis, and assays for bioactive contents of 24 samples of C. cinereum from different locations were evaluated to determine the standard information of the plant material. Results: The result showed the microscopic characteristic of pollens in all powder samples. No nicotine content in C. cinereum extract was observed with LC-MS; apigenin and luteolin were instead selected as markers. The observed average contents of apigenin and luteolin were 0.238 and 1.059 mg/g, respectively, using HPLC-UV. Nitrite and nitrate components in C. cinereum, which induced flavor aversion leading to smoking cessation, were determined. The average nitrite and nitrate content were 0.004 and 0.526 mg/kg in ethanol extract and 0.014 and 1.645 mg/kg in the water extract, respectively. The results did not substantiate the concern for high potassium content in C. cinereum materials for cardiovascular and renal patients where only traces were observed in all samples (3.113 and 20.898 mg/kg in ethanol and water extracts, respectively). Conclusion: The results can be used to establish the specification of C. cinereum, which will be useful for quality control of the raw material. This new information is crucial and can be utilized extensively prior to herbal product preparation.
Keywords: standardization